Leaf-cutting ant faecal fluid and mandibular gland secretion: effects on microfungi spore germination - Rodrigues, Andre [UNESP]; Carletti, Carla D. [UNESP]; Bueno, Odair C. [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Soc Brasileira Microbiologia, 2008)
The mandibular gland secretion (MGS) and the faecal fluid (FF) of the leaf-cutting ant Atta sexdens rubropilosa Forel affected the spore germination of selected microfungi isolated from nests of this insect. MGS was more effective than the FF, completely inhibiting the spore germination of four out of six microfungi species.

O fluído fecal (FF) e a secreção da glândula mandibular (MGS) de operárias da formiga cortadeira Atta sexdens rubropilosa Forel afetaram a germinação dos esporos de microfungos isolados dos formigueiros. MGS foi mais eficiente que FF, inibindo quatro espécies de microfungos dentre as seis estudadas.
O fluído fecal e a secreção da glândula mandibular de formiga cortadeira: efeitos sobre a germinação de esporos de microfungos
Keywords: fungus garden; microorganisms; Atta